Determinants of Government Budget Deficit in the Economy of Iran Emphasizing the Economic and Political Economic Factors - Alireza Saedi Sarkhanlou; Hassan Dargahi (برنامه‌ریزی و بودجه, 2021)
In order to implement structural reform in the government budget of Iran, it is necessary to analyze the budgetary characteristics. This paper attempts to identify the determinants of budget deficit by using ARDL modeling based on the Iranian budget records for the period 1964-2020. Theoretical and empirical evidence both show that three main factors including budgeting structure, macroeconomic situation, and political economic forces could play a definite role in the budget deficit. Long term estimated coefficients of the research models explain that budget deficit will be worsened with bigger size of government, and with the increase in the government expenditure dispersion in comparison with the government revenues dispersion, also with a bigger share of public investment in total investment, and finally with wider GDP gap and inflation gap. Correspondingly, more inequality of income leads to a bigger deficit. The results also indicate that in the economy of Iran expenditures are a driving force that brings about the budget deficit. It is evident that in a resource-based economy, an increase in revenues of resource exports would relocate the economy to the positive output gap and boom cycle that in turn will push governments to a higher level of expenditures and a budget deficit. During the recession period in which government revenues decline, the recurrent expenditures resist adjustment due to its sticky behavior, hence the deficit gets worse. Meanwhile, political economic factors such as weakness of the government power and pressure by interest groups, all together have magnifying effects on worsening the budget deficit. During the era that foreign reserves in Stabilization Account and National Development Fund were enough to compensate deficits, the presence of the wealth effect on government expenditures, and thus on the budget deficit, is confirmed.